5 questions on design thinking - McDonald, Nikki (O'Reilly Media, 2017)
"Five Questions is a series where we sit down with leading industry practitioners and ask them for real-world stories and examples of how they're using technology in their everyday work. In this interview, O'Reilly Content Director Nikki McDonald talks with Naveen Raja, UX designer and strategist at Neighborhoods.com, about design thinking."--Resource description page